Pengaruh ROA, CR, DER, dan Operating Leverage Terhadap Return Saham Perbankan Syariah - Sulthan Naufal Zaidane; Radia Purbayati; Fatmi Hadiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the effect of company performance factors, including Return Of Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER) and Operating Leverage on stock returns with a case study of PT. Panin Dubai Syariah, Tbk in the period 2018-2020. This research is a quantitative research with a descriptive approach and sourced from the official website of the company PT. Panin Dubai Syariah, Tbk. The data analysis technique used is multiple linear regression and the data analysis application used is SPSS v24. The results showed that DER partially affected the stock return of PT. Panin Dubai Syariah, Tbk, while the ROA, CR, and Operating Leverage variables have no significant effect on the stock return of PT. Panin Dubai Syariah, Tbk. Simultaneously DER, ROA CR and Operating Leverage have a significant impact on stock returns, where the performance factor of liability to equity fundamentals (DER) is the most dominant factor on stock returns at PT. Panin Dubai Syariah, Tbk.